Pelaksanaan Perjanjian Kerjasama Antara PT Jaklingko Mikrotrans Dengan PT Transjakarta dalam Pemberian Upah Kepada Pramudi - Radot Gilbert Putra Limbong; I Made Sarjana (Ethics and Law Journal: Business and Notary, 2024)
This research is motivated by the gap between das sollen and das sein, namely the difference between applicable legal norms and reality. The rule that has experienced a gap is DKI Jakarta Governor Regulation Number 96 of 2018 concerning the Integration of Feeder Transportation into the Bus Rapid Transit System. The problem raised in this study is how the implementation of the cooperation agreement between Jaklingko Mikrotrans and PT Transjakarta is related to the provision of wages to the driver, as well as the factors that cause the discrepancy in the provision of wages. The method used is empirical legal research with a statutory approach and factual approach. Primary data sources were obtained from interviews with respondents and informants, while secondary data came from literature, journals, the internet, and laws and regulations. Data collection techniques were conducted through interviews and document studies, with qualitative analysis. The results showed that the implementation of the cooperation agreement was not appropriate due to the reduction of mileage from 200 Km to 170-180 Km per day, to the detriment of the driver. The internal factor of wage discrepancy is unilateral policy, while the external factor is budget changes from the DKI Jakarta Provincial Government without adjusting the Rp/Km price in the agreement. Abstrak Penelitian ini dilatarbelakangi oleh adanya kesenjangan antara das sollen dan das sein, yaitu perbedaan antara norma hukum yang berlaku dengan kenyataan. Aturan yang mengalami kesenjangan adalah Peraturan Gubernur DKI Jakarta Nomor 96 Tahun 2018 tentang Integrasi Angkutan Pengumpan ke dalam Sistem Bus Rapid Transit. Permasalahan yang diangkat dalam penelitian ini adalah bagaimana pelaksanaan perjanjian kerjasama antara Jaklingko Mikrotrans dengan PT. Transjakarta terkait pemberian upah kepada pramudi, serta faktor-faktor yang menyebabkan ketidaksesuaian pemberian upah tersebut. Metode yang digunakan adalah penelitian hukum empiris dengan pendekatan perundang-undangan dan pendekatan fakta. Sumber data primer diperoleh dari wawancara dengan responden dan informan, sementara data sekunder berasal dari literatur, jurnal, internet, dan peraturan perundang-undangan. Teknik pengumpulan data dilakukan melalui wawancara dan studi dokumen, dengan analisis kualitatif. Hasil penelitian menunjukkan bahwa pelaksanaan perjanjian kerjasama tidak sesuai karena pengurangan jarak tempuh dari 200 Km menjadi 170-180 Km per hari, sehingga merugikan pramudi. Faktor internal ketidaksesuaian upah adalah kebijakan sepihak, sedangkan faktor eksternal adalah perubahan anggaran dari Pemerintah Provinsi DKI Jakarta tanpa penyesuaian harga Rp/Km dalam perjanjian. Kata Kunci: Perjanjian Kerjasama, Pelaksanaan, Pramudi, Upah.